Highly efficient optical parametric oscillators in the mid-IR - Thilmann, Nicky (KTH, Laserfysik, 2014)
This thesis shows how sources of coherent radiation in the mid-infrared (mid-IR) region can be enhanced. To achieve this, optical parametric oscillators (OPOs) employing improved novel materials, new optical elements, and novel cavity designs have been implemented. Moreover, important measurements for the development of ultrashort-pulsed lasers were conducted. In turn, such lasers are suitable pump sources for the nonlinear conversion to the mid-IR. The mid-infrared spectral region is of interest for many applications in the areas of medicine, sensing, climate monitoring, and ranging. Here the target wavelength 6.45μm was especially interesting since it is considered particularly useful in surgical applications. Commercially available lasers perform poorly as pump sources for the generation of this wavelength. Therefore, a superior cascaded conversion scheme with large aperture crystals was implemented. In these, Rb-doped KTiOPO4(KTP) was employed since it was found that Rb-doping improves the poling properties of KTP. Moreover, for the conversion scheme to be efficient, a narrow-band out putspectrum of the OPO is required. It was shown here that this can successfully be achieved by utilizing a volume Bragg grating (VBG). Alternatively, for the direct generation of mid-IR radiation, KTiOAsO4(KTA) crystals with an extended transmission into the mid-IR as compared to KTP have been investigated. Novel room-temperature periodic-poling of KTA was shown and the fabricated crystals were successfully employed in a highly-efficient OPO. The newly developed pump sources based on the Rb-doped KTP crystals were successfully implemented in a cascaded OPO experiment. Here, a so-called RISTRA cavity was employed and high-energy nanosecond pulses at 6.45μm with improved beam quality were demonstrated. Pulsed lasers emitting at around 1μm, e.g. Yb-doped host materials, are frequently employed as pump sources of nonlinear optical conversion schemes. To allow further development of ultrashort pulsed Yb-doped double tungstate lasers, the nonlinear refractive index of several materials was measured. Among these are new materials which were for the first time characterized with regard to their nonlinear refractive index. In addition to the pulsed experiments above, a periodically poled lithium niobate crystal was employed to generate continuous-wave output. Even here, a volume Bragg grating was implemented and thereby demonstrated a novel method to control the threshold of the OPO. Thus, a stable high-energy highly-efficient OPO could be demonstrated. === QC 20141203